PANDEMIC OASIS: POPULAR RELIGIOSITIES AS WOMEN’S LIFE-GIVING COMMUNITAS - K.F. Chan (Acta Theologica)
This article argues and explores how popular Catholic piety can serve as an agent to create life-giving communitas for women in Macao, China. This research uses the narratives of six Catholic women about how their immersion in various public and private devotional practices creates solidarity and communities that are inclusive, empowering, and nurturing during the outbreak of COVID-19. Besides petitioning their long-lasting devotional images such as St Roch and Our Lady of Fatima, women learn and move on to a new model of online and live stream religious response and ritual innovations at the time of coronavirus in Macao. The digitisation of gathering strengthens the global connection among women to the rest of the world, shapinga new form of devotional culture and community ties that are not necessarily institutionalised. Devotional practices act as a spiritual oasis, personally and communally, for women coming together and bring hope, strength, and consolation to this unprecedented time.